INDESEM | The International Design Seminar Emergence, Development, and Interplay with the Education in Delft - Zech, Valentin (TU Delft Open, 2022)
The International Design Seminar (INDESEM) has a long and fascinating history. Since the first edition in 1964, each INDESEM has brought students and professionals from all over the world together to explore one relevant architectural issue of their time - in the form of excursions, competitions, and lectures. While INDESEM evolves and changes, depending on the people involved in its organization, each edition exposes current ideas and needs of the students: their views on architecture education, what they deem most relevant, and which designers inspire them. In return, INDESEM inspires educators and helps establish new ways of teaching in architecture. This book presents archive material, publications and interviews with some of the key personalities to tell this exciting story for the first time.